I have a dream - King, Martin Luther, Jr., 1929-1968. (New York : Scholastic, 1997)
Text of the speech given by Dr. Martin Luther King, Jr. on August 28, 1963 describing his visionary dream of equality and brotherhood for humankind. Also includes illustrations by award winning artists depicting scenes described in the speech.
Wilson's Children.
Elem. School Library Collection.
School Library Journal.
8.5
3-6
Keywords: African Americans -- Civil rights; Civil rights movements -- United States -- History -- 20th century; African Americans -- Civil rights; Civil rights movements; African Americans -- Civil rights; Civil rights movements -- History; United States -- Race relations; United States -- Race relations; United States -- Race relations